Assistance in Utilizing E-student worksheets Teaching Materials with Live Worksheet Application Support for Critical Thinking in Elementary School Teachers - Awida Awida; Rendy Nugraha Frasandy; Rani Juwita (Universitas Lambung Mangkurat, 2024)
Current teaching practices still rely on printed images and text materials. This is due to the need for educators' ability to develop digital-based learning materials, resulting in students often becoming bored during lessons. Additionally, the abstract nature of the learning material often requires further explanation. This community service aims to assist elementary school teachers in utilizing e-student worksheets teaching materials with the support of the Live Worksheet application. This community service employs the Community Based Research (CBR) model through training and mentoring. The results show an improvement in the competency of elementary school teachers in utilizing e-student worksheets as teaching materials.